Client Preferences: Building Bridges Between Therapy and Everyday Life - John McLeod (Psychotherapy and Counselling Journal of Australia)
Recent research has shown that taking account of client preferences has a significant positive impact on the outcomes of therapy and reduces client drop-out. Findings from relevant studies, conducted within different research methodologies, are reviewed. Examples are provided of strategies for exploring client preferences and ways of using this knowledge to inform the process of therapy. Effective utilization in therapy of client preferences, strengths and resources requires the adoption of a collaborative, dialogical stance, and an interest in the everyday life of the client. The implications of these ideas for therapy research and practice are discussed. This paper is based on material presented at a keynote lecture, PACFA, CAPA and AARC Annual Conference, Sydney, 14th June 2014